Aromatic hydrocarbon degradation of biofilm formed by microorganisms on cellulose material at 50 litre modules - Cong, Le Thi Nhi; Mai, Cung Thi Ngoc; Tuan, Do Van; Quyen, Dong Van (Vietnam Journal of Biotechnology, 2018)
Biofilms are defined as community of microorganisms which are irreversibly or reversibly attached on solid surfaces. These microorganisms are embedded in a self-produced exopolysaccharide matrix, and exhibit different growth and bioactivity compared with planktonic cells. With their high biomass density, stability, and potential for biodegradation of recalcitrant compounds contained in oil contaminated wastewater such as aromatic hydrocarbons. Aromatic hydrocarbons are the main constituents of petroleum and its refined products. These compounds are also quantitatively the main environmental pollutants worldwide. In this report, cellulose material was used as a carrier for forming biofilm by microorganisms to remove of these components. Cellulose material is considered as inexpensive, available, sustainable, little waste production and can be recycled. As a result, the microorganisms were successful to adhere on cellulose material at 50 liter module with cell density of 4.3x108 CFU/ml after 7 day-incubation. Under the scanning electron microscope with the 1500 magnification, the microbial cells had a very high density, closely linked together and firm adhesion on the cellulose material. The mixture species biofilm attached on cellulose carrier at 50 liter module had the ability to degrade 80.1, 78.3, 60.0, 98.5 and 91.2% of anthracene, fluorene, naphthalene, phenol and pyrene after 7 days, respectively. The obtained results showed that biofilm formed by multiple bacterial strains attached on cellulose material may considerably increase the degrading efficiency of aromatic hydrocarbon compounds. The results also indicated that cellulose material is suitable carrier to choose in removal of aromatic hydrocarbon contaminated wastewater. These results are considered as new approach to apply microbial films on cellulose material to degrade oil polluted waste-water in the environment.